RANCANG BANGUN DASHBOARD KEPEGAWAIAN SEKOLAH TINGGI ILMU EKONOMI MUSI RAWAS (STIE MURA) LUBUKLINGGAU - Davit Irawan; Asep Toyib Hidayat (LPPM STMIK Pringsewu, 2019)
The problem in this research is the process of employee data processing at the MusiA Rawas Economics School (STIE MURA) Lubuklinggau is still done semi-manually by using Microsoft Word and Excel so that employee data processing is still less effective and time-consuming. This research uses knowledge management methods. The results showed that the design program was an online dashboard application using the PHP programming language and MySQL database and Adobe Dreamweaver CS3 as the media for writing program listings. This research can be concluded that this web-based application can produce information to improve the quality of employee data processing quickly, effectively and efficiently. This is what was done by researchers in this research study. This research will produce a prototype product and the results of this research will be published in a non-accredited national journal.